Prospects of developing innovative minufacruring of the full cycle of VI economic structure in Russia - M. Y. Bikov; D. V. Timokhin (Путеводитель предпринимателя, 2020)
The article analyzes the degree of institutional and economic readiness of the Russian aggregate manufacturer to the transition to a new technological concept of the organization of the production process. The strengths and weaknesses of the Russian economy as a participant in the expected competitive processes in the field of global innovation are identified.